Instantaneous speckle reduction? Yes, but there is no free lunch! - Häusler, Gerd; Dötzer, Florian; Mantel, Klaus (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We are motivated by the question if scanning laser projection with low speckle noise is possible. Scanning laser projection requires "instantaneous" speckle reduction, within a few nanoseconds-meaning that no moving diffusors can be used. We will argue that instantaneous speckle reduction is possible by conversion of spatial coherence to spatial incoherence-but nature demands for a compensation. The cost can be estimated via the information theoretical concept "channel capacity", which incorporates the etendue as well as the signal-to-noise ratio. We will show that an optical system with low spatial coherence (=low speckle noise) must provide significantly more degrees of freedom than a coherent imaging system. The consequence for the technical optical system is serious: Significant speckle reduction can only be achieved by an excessively large projection aperture. This is not just a sophistic consideration, it seriously restricts the design of scanning laser projectors.
Created from Fastlane, Scopus look-up
Keywords: Channel capacity; Etendue; Laser projection; Speckle noise; Speckle noise reduction